2021
DOI: 10.1097/pgp.0000000000000812
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Protein Overexpression and Gene Amplification in Tubo-Ovarian High-grade Serous Carcinomas

Abstract: Individual and in-training subscription rates include print and access to the online version. Institutional rates are for print only; online subscriptions are available via Ovid. Institutions can choose to purchase a print and online subscription together for a discounted rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Various studies[ 6 - 10 ] have demonstrated that the HER2 gene is overexpressed in multiple tumor types, including breast, lung, ovarian, prostate, and colorectal cancers. Around 20% of the patients with gastric cancer exhibit HER2 overexpression; these HER2-positive patients tend to have poor prognoses and are at higher risk of recurrence[ 5 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies[ 6 - 10 ] have demonstrated that the HER2 gene is overexpressed in multiple tumor types, including breast, lung, ovarian, prostate, and colorectal cancers. Around 20% of the patients with gastric cancer exhibit HER2 overexpression; these HER2-positive patients tend to have poor prognoses and are at higher risk of recurrence[ 5 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…82,[86][87][88][89] HER2-positivity rates are much lower in ovarian high-grade serous carcinoma than in USC, with overexpression/amplification seen in only 2%-4% of cases, and low response rates in those treated with targeted therapy. [91][92][93] Limited data also suggest low HER2positivity rates in ovarian carcinosarcoma, at less than 10%. 90 Higher rates of HER2 overexpression/ amplification have been reported in ovarian mucinous tumours, mostly mucinous carcinomas with concurrent TP53 mutations.…”
Section: Her2 Biomarker Expression In Other Gynaecologic Malignanciesmentioning
confidence: 99%
“…HER2‐positivity rates are much lower in ovarian high‐grade serous carcinoma than in USC, with overexpression/amplification seen in only 2%–4% of cases, and low response rates in those treated with targeted therapy 91–93 . Limited data also suggest low HER2‐positivity rates in ovarian carcinosarcoma, at less than 10% 90 .…”
Section: Her2 Scoring Systems and Readouts In Human Solid Tumoursmentioning
confidence: 99%
“…Protein expression studies on PD-L1, LAG3 and potential use of immunotherapeutic modalities on ovarian HGSCs have demonstrated modest therapeutic results and controversial prognosis [60][61][62]. Other dysregulated pathways in HGSCs are the PIK3CA/AKT and NOTCH pathways which can be therapeutically targeted by using PIK3CA or AKT inhibitors [63,64], whereas HER2 overexpression/ amplification (2-4% in HGSCs) has no significant impact on prognosis, albeit a finding that can be exploited for anti-HER2 targeted therapy [65,66].…”
Section: Molecular Pathology Of Ovarian High-grade Serous Carcinomasmentioning
confidence: 99%